Effects of wind energy development on nesting ecology of Greater Prairie-Chickens in fragmented grasslands - McNew, Lance B.; Hunt, Lyla M.; Gregory, Andrew J.; Wisely, Samantha M.; Sandercock, Brett K. (My University, 2014)
Wind energy is targeted to meet 20% of U.S. energy needs by 2030, but new sites for development of renewable energy may overlap with important habitats of declining populations of grassland birds. Greater Prairie-Chickens (Tympanuchus cupido) are an obligate grassland bird species predicted to respond negatively to energy development. We used a modified before–after control–impact design to test for impacts of a wind energy development on the reproductive ecology of prairie-chickens in a 5-year study. We located 59 and 185 nests before and after development, respectively, of a 201 MW wind energy facility in Greater Prairie-Chicken nesting habitat and assessed nest site selection and nest survival relative to proximity to wind energy infrastructure and habitat conditions. Proximity to turbines did not negatively affect nest site selection (β = 0.03, 95% CI = −1.2–1.3) or nest survival (β = −0.3, 95% CI = −0.6–0.1). Instead, nest site selection and survival were strongly related to vegetative cover and other local conditions determined by management for cattle production. Integration of our project results with previous reports of behavioral avoidance of oil and gas facilities by other species of prairie grouse suggests new avenues for research to mitigate impacts of energy development.
Keywords: Before–after control–impact; Grassland bird; Habitat use; Nest placement; Nest survival; Tympanuchus; Wind power; Greater prairie chicken